O papel da instrução com foco na forma (iff) para correção de erros gramaticais na interlíngua de aprendizes de espanhol/le - Silva, Laysi Araújo da (2018)
This work aims to study the interlanguage of Spanish learners of a distance-learning degree in the Spanish language. In order to investigate the role of Instruction with Focus on Form to overcome errors in the use of forms and verbal tenses in written productions These learners. The study was based more specifically on the theoretical conceptions of Chomskyan linguistics, on the cognitive theories of learning under the auspices of Interlingua de Selinker (1972) and on the Analysis of Errors OF CORDER (1967) and FERNÁNDEZ (1997). Also discussed were the reflections proposed by ELLIS (1997a) and LARSEN-FREEMAN (1991) on the role of formal instruction in the process of acquiring an L2. In addition, we have used other studies that investigated Instruction with Focus on Form in order to situate this research among others in this theme. In order to reach our goal, we undertook an action research, whose data were submitted to qualitative-descriptive analysis. First, we observed and analyzed the written productions of 20 (twenty) students of this degree while studying the subjects - Spanish Language V and Spanish Language VI - in two subsequent semesters. Based on the errors identified in the written productions during this period of observation, we elaborated the didactic intervention proposal - a holiday course called "Verbs in Spanish". For the course, we elaborated 5 units employing the methodology of Instruction with Focus on Form; The units set out to work on the problems identified in the use of Spanish forms and tenses. The text written in Unit 1 was used as a pre-test and the written production of Unit 5 as a post-test. The data collected during the observation phase during the Spanish Language classes V and VI indicate that the most frequent errors in the written interlanguage of our participants were those of choice of verbal time, failure of conjugation and application of irregularity rule, spelling Of the verb, or of non-conjugation of verbal time appropriate to the situation. We also show errors of verbal agreement, use of pronominal verbs, and use of the verbal mode. We also found that the indicative mode presented more errors than the other modes, perhaps because it was the most frequently used by the participants during the observation phase. We also identified that most of the errors were due to the negative transference of the mother tongue to the target language, in this case Spanish. These evidences allow us to characterize the interlanguage of our participants as being at a stage where there are still many errors in the use of the times and verbal forms resulting from negative transference of the mother tongue. The analysis of the written productions of the students during the intervention phase allows us to say that the Instruction with Focus on Form (IFF)has proved to be beneficial as it has returned the learners' attention to the formal aspects of the target language and, consequently, to Learning the language in focus. The comparison between the mistakes made in the written tests of the pre-test and those committed in the posttest did not, however, show relevant differences between the results of the pre-test and the post-test. The analyzed data showed that both types of errors of use of tenses and the most frequent cause for the occurrence of these errors were maintained. Thus, we can not make assertions as to the effectiveness of the IFF to correct identified errors, due to the complexity, extent and variety of content involved in the holiday course in the intervention phase. Many verbal tenses were addressed, as well as working mode, concordance and pronominal verbs. This made it impossible for us to have more time to practice. Although we can not quantify the efficiency of the IFF in the proposed intervention, we noticed, at the end of the course, qualitative results of improvement in the quality of students' written texts. The knowledge gained from the Instruction with Focus on Form enabled the participants to insert in their written productions more textual elements, even if these productions still lacked linguistic acuity.